Information measuring subsystem oil pumping station "Parabel"; MATEC Web of Conferences; Vol. 19 : The 2nd International Youth Forum "Smart Grids", Tomsk, Russia, October 6-10, 2014 - Nyashina G. S. Galina Sergeevna (2014, 2014)
Title screen